Natural killer cells kill human melanoma cells with characteristics of cancer stem cells - Pietra, G.; Manzini, C.; Vitale, M.; Balsamo, M.; Ognio, E.; Boitano, M.; Queirolo, P.; Queirolo, P.; Mingari, M.C.
Experimental and clinical data suggest that tumours harbour a cell population retaining stem cell characteristics that can drive tumorigenesis. CD133 is considered an important cancer stem cells (CSC)-associated marker. In a large variety of human malignancies, including melanoma, CD1331 cells have been reported to comprise CSC. In this study, we show that melanoma cell lines are highly heterogeneous for the expression of several stem cell-associated markers including CD133, c-kit/CD117 and p75 neurotrophin receptor/CD271. Since no information is available on the ability of NK cells to recognize and lyse melanoma stem cells, we assessed whether melanoma cell lines, characterized by stem cell-like features, were susceptible to lysis by IL-2-activated NK cells. We show that activated NK cells efficiently kill malignant melanoma cell lines that were enriched in putative CSC by the use of different selection methods (i.e. CD133 expression, radioresistance or the ability to form melanospheres in stem cell-supportive medium). NK cell-mediated recognition and lysis of melanoma cells involved different combinations of activating NK receptors. Since CSC have been reported to be both drug resistant and radioresistant, our present data suggest that NK-based adoptive immunotherapy could represent a novel therapeutic approach to possibly eradicate metastatic melanoma.